2019
DOI: 10.1163/18759866-20191406
|View full text |Cite
|
Sign up to set email alerts
|

The invasive alien freshwater flatworm Girardia tigrina (Girard, 1850) (Platyhelminthes, Tricladida) in Western Europe: new insights into its morphology, karyology and reproductive biology

Abstract: Invasions of alien species form one of the major threats to global biodiversity. Among planarian flatworms many species are known to be invasive, in several cases strongly affecting local ecosystems. Therefore, a detailed knowledge on the biology of an invasive species is of utmost importance for understanding the process of invasion, the cause of its success, and the subsequent ecological impact on native species. This paper provides new information on the biology of introduced populations of the freshwater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In these examples, sexualization was induced in response to a clear and definable change in temperature or in food, whereas our G. gua animals were maintained in a temperature controlled environment and fed a consistent diet of calf liver (see Materials and Methods). Spontaneous sexualization of G. tigrina laboratory animals has been reported on multiple occasions (17,40) and examples of these events share some similarities with our observation in G. gua, such as an immature copulatory apparatus and sterility. Nevertheless, these reports describe some features that we did not readily observe in our limited number of putatively sexual G.gua, such as hyperplastic ovaries and the presence of supernumerary copulatory apparatuses.…”
Section: Discussionsupporting
confidence: 87%
“…In these examples, sexualization was induced in response to a clear and definable change in temperature or in food, whereas our G. gua animals were maintained in a temperature controlled environment and fed a consistent diet of calf liver (see Materials and Methods). Spontaneous sexualization of G. tigrina laboratory animals has been reported on multiple occasions (17,40) and examples of these events share some similarities with our observation in G. gua, such as an immature copulatory apparatus and sterility. Nevertheless, these reports describe some features that we did not readily observe in our limited number of putatively sexual G.gua, such as hyperplastic ovaries and the presence of supernumerary copulatory apparatuses.…”
Section: Discussionsupporting
confidence: 87%
“…(Guanajuato) animals that exhibited some evidence of spontaneous sexualization, including the development of ovaries and testes. Spontaneous sexualization of G. tigrina laboratory animals has also been reported on multiple occasions [17,41] and these specimens share some similarities with the rare sexualized G.sp . (Guanajuato) animals we studied, such as an immature copulatory apparatus and sterility.…”
Section: Discussionmentioning
confidence: 98%
“…Most likely, the latter were effectuated through the international trade in aquatic plants and the activity of aquarists or through the importation and subsequent culturing of North American strains of G. tigrina and G. dorotocephala as model organisms in education and scienti c studies all around the world. The fact that G. tigrina is very sticky, clearly enhances its attachment to all kinds of surfaces and thereby facilitates its passive dispersal (Stocchino et al 2019). Wright (1987) suggested that multiple occasions of disposal of the contents of aquaria and of small ornamental garden ponds into local rivers might underlie the pattern of distribution of G. tigrina in Great Britain.…”
Section: Three North American Species Of Girardia Colonise the Worldmentioning
confidence: 99%
“…The species Girardia tigrina (Girard, 1850) was rst reported in Germany in the 1920's, after which it was recorded also from other parts of mainland Western Europe, as well as the Balearic Islands and the Azores, its spread most likely effectuated through the international trade in aquatic plants and the activity of aquarists (Stocchino et al 2019 and references therein). Representatives of the genus have been reported also from Australia, Japan, and Hawaii (Kawakatsu et al 1984 For a long time, it has been assumed that only G. tigrina was introduced in Europe, although some studies have pointed to the possibility that other alien Girardia species may be present, in view of the diversity in morphology, karyology, and reproductive biology of the populations analysed from the Iberian Peninsula (Ribas, Riutort, and Baguñà 1989) and Italy (Benazzi 1993;Stocchino et al 2019). However, due to the fact that, generally, the introduced populations of Girardia show only asexual reproduction and do not possess a copulatory apparatus, their identi cation to species level is greatly hampered, since the main diagnostic characters reside in the reproductive structures (Sluys and Riutort 2018).…”
Section: Introductionmentioning
confidence: 99%